Pengaruh Startegi Pebelajaran Kooperatif Model Snowball Throwing Terhadap Hasil Belajar Siswa Pada Materi Siswa Pencernaan Makanan Kelas XI: (The Effect of The Snowball Throwing Model's Cooperative Learning Strategy on Student Learning Outcomes on Class Xi Food Digestion Student Material) - Rizki Putri Ananda Srg Rizki Putri Ananda Srg; Wulan Purnama Sari Vinia Wulan Purnama Sari Vinia; Deni Puspita Sari Deni Puspita Sari; City Qurnia Sari Pohan City Qurnia Sari Pohan; Siti Fauziah Siti Fauziah; Dwike Amalia Azzahra Dwike Amalia Azzahra (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2023)
This research begins with the phenomenon revealed in the data on science ability on an international level that Indonesia is ranked 50 out of 57 countries. This is an indication that students' learning abilities are still in the low category and must be improved. In addition, according to data on learning outcomes at SMAS Budisatrya Medan, many are below the KKM. This condition is influenced by learning models that are less varied, student activity has decreased and exploration of information is not optimal. The purpose of this study was to determine whether the application of the cooperative learning model with snowball throwing was able to improve student learning outcomes in class XI IPA 1 at SMAS Budisatrya. This research is in the form of a quasi-experiment with a pretest-posttest group design model. To test the hypothesis, it is done with Independent sample t test and N-Gain test. The result turned out to have a positive effect on the increase in student learning outcomes. Key words: Cooperative Learning Strategy Snowball Throwing Model, Food Digestion, Science, Learning Outcomes Â ABSTRAK Penelitian ini diawali dengan adanya fenomena yang diungkap dalam data kemampuan IPA secara peringkat Internasional bahwa Indonesia berada pada peringkat 50 dari 57 negara. Hal tersebut menjadi indikasi bahwa kemampuan belajar siswa masih dalam kategori rendah dan harus ditingkatkan. Selain itu sesuai dengan data hasil belajar di SMAS Budisatrya Medan banyak dibawah KKM. Kondisi tersebut dipengaruhi oleh model pembelajaran yang kurang bervariatif, keaktifan siswa mengalami penurunan dan eksplorasi informasi yang tidak maksimal. Tujuan penelitian ini untuk mengetahui apakah penerapan model pembelajaran kooperatif dengan snowball throwing mampu meningkatkan hasil belajar siswa kelas XI IPA 1 di SMAS Budisatrya. Penelitian ini berbentuk eksperimen semu dengan model pretest-postest group design. Untuk pengujian hipotesisnya dilakukan dengan Independent sample t test dan uji N-Gain. Hasilnya ternyata berpengaruh positif terhadap kenaikan hasil belajar siswa. Kata kunci: Strategi Pembelajaran Kooperatif Model Snowball Throwing, Pencernaan Makanan, IPA, Hasil Belajar